Avaliação da resistência à fadiga e caracterização microestrutural de fios extrudados e forjados da liga AA7050 reciclada por conformação por spray - Salvo, João Guilherme Jacon de (Universidade Federal de São Carlos, 2016)
High strength 7XXX precipitation hardened aluminum alloys are widely used in aircraft structural components. The machining process applied in the fabrication of these components is a low efficiency process regard ing material utilization, generating a solid waste composed by noble alloy machining chips with great potential of application. However, this material is usually sold as scrap for the secondary aluminum industries, which use it for low performance applications. The present work is a continuation of the effort provided by others researchers, who have been searching a higher value-added destination for this material through its reintroduction as a high quality and high strength final product, whose proprieties are compatible with those provided by the original alloy. Although, traditional foundry practices are unsuitable for this purpose, resulting in a poor quality material. Hence, this study aims to characterize a wire produced by a process route comprising AA7050 machining chips spray forming remelting, followed by extrusion and swaging; resulting in a 2.7 mm diameter wire. The microstructural characterization was carried out by scanning electronic microscope (SEM), transmission electronic microscope (TEM), x-ray diffraction (XRD) and differential scanning calorimetry (DSC). The mechanical properties were evaluated by tensile and fatigue tests. Fracture surface analyses were carried out by SEM. The results allowed correlating wire microstructure, through alloy intermetallics characterization, with its monotonic and cyclic mechanical properties. It was possible to verify the microstructural effects in fracture behavior of the tested wires. The AA7050 alloy wires showed high tensile and fatigue (HCF) strength, with possible applications in power transmission cables and, even, their reintroduction in the aerospace industry.
Fatigue strength evaluation and microstructural characterization of extruded and rotary swaged AA7050 wires recycled by spray forming
Keywords: Al-Zn-Mg-Cu; Conformação por spray; Processamento termomecânico; Microestrutura; Fadiga; Spray forming; Thermomechanical processing; Microstructure; Fatigue; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO::CONFORMACAO MECANICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO::FUNDICAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO::TRATAMENTO TERMICOS, MECANICOS E QUIMICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::ESTRUTURA DOS METAIS E LIGAS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::PROPRIEDADES MECANICAS DOS METAIS E LIGAS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::TRANSFORMACAO DE FASES